The Effect of Etnopedagogy Learning Model on Student Character Development in the Pandemic Era - Wanhar, Fira Astika; Hasibuan, Ainul Marhamah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to identify differences in the character development of students taught by ethnopedagogy methods compared to conventional learning models. The method used in this research is quasi-experimental. The research was carried out at SD Negeri 101777 which is located at the Village of Saintis, Percut Sei Tuan District, Deli Serdang Regency. The population of this study were all students of SD Negeri 101777. The sample used was 32 students in class V, consisting of 16 students in class V/a as the experimental class and 16 students in the control class V/b. The data collection technique is the student character development test. The data analysis technique used an independent sample t test with a significant level of of 0.05. The results showed that: the character development of students who were taught with the ethnopedagogical learning model was higher than the students who were taught using the conventional learning model.